Sodium-ion battery flame-retardant electrolyte with high cycling stability and preparation method of sodium-ion battery flame-retardant electrolyte

By using sulfonic acid modified carbon black in sodium ion battery electrolyte and Zn-MOF and loading ionic liquid, the problems of flammability and insufficient flame retardant capacity of the electrolyte are solved, and an electrolyte with high cycle stability and good flame retardant performance are achieved.

CN119601776AActive Publication Date: 2025-03-11ANHUI UNIV

Patent Information

Application Number
CN202510144567.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

In the existing sodium ion battery electrolyte, carbonate solvents are flammable, resulting in a large safety hazard and poor flame retardant capacity, which affects the cycle stability of the battery.

Method used

By compounding the sulfonic acid-modified carbon black with Zn-MOF and loading the ionic liquid into the pores of Zn-MOF, the flame retardant and ion transport performance of the electrolyte are improved, and the circulation stability of the electrolyte is improved.

Benefits of technology

The high cycle stability and good flame retardant performance of sodium ion battery electrolyte are achieved, ensuring the safety and performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery flame-retardant electrolyte with high cycle stability and a preparation method thereof, and the sodium-ion battery flame-retardant electrolyte comprises the following components in percentage by mass: 70-75% of an organic ester solvent, 8-12% of sodium salt, 2.5-3.5% of triethyl phosphate, 4.5-5.5% of ionic liquid loaded powder and 5-10% of a sulfur-containing additive, the prepared sodium-ion battery flame-retardant electrolyte is good in conductivity, the prepared sodium-ion battery is high in cycling stability and good in flame retardance, the flame retardance of the flame-retardant electrolyte is improved through compounding of the Zn-MOF and the modified carbon black, the conductivity of the electrolyte is improved through the Zn-MOF and the ionic liquid in the Zn-MOF, and the prepared ionic liquid powder is high in stability and good in flame retardance. The dispersity in a carbonic ester solvent is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and specifically relates to a flame retardant electrolyte for sodium ion batteries with high cycle stability and a preparation method thereof. Background Art

[0002] Sodium ion batteries stand out for their rich sodium resources and low cost. Sodium ion battery electrolyte is an important component of sodium ion batteries, which has a significant impact on the cycle performance and safety of sodium ion batteries. Among the solvents of sodium ion battery electrolytes, carbonate solvents have good wetting of diaphragms and electrode materials and high ionic conductivity, and are widely used electrolyte solvents. However, carbonate electrolytes are very flammable and prone to exothermic reaction chains, which generate excessive heat and oxygen to ignite the vapor of the electrolyte, seriously affecting the safety of battery use. The electrolyte needs to be flame-retardant modified, but excessive addition of flame retardants will cause the electrolyte conductivity to decrease, affecting the cycle performance of sodium ion batteries. Patent CN118263527A discloses a high-voltage long-cycle ester-based sodium ion battery electrolyte and a sodium ion battery, which is compounded by sodium salt, organic ester-based solvent and sulfur-containing additive, so that the sulfur additive generates a sulfur-containing inorganic interface film with high conductivity, thereby improving the cycle performance of the battery; however, it only improves the cycle stability of the sodium ion battery, and its flame retardant ability is poor, and the organic ester solvent is flammable, which poses a great safety hazard. Patent CN114464885A discloses a method for preparing a flame-retardant sodium-ion battery electrolyte and a safe sodium-ion battery, in which an organic phosphate solvent, a fluorinated ether diluent, an additive and a sodium salt are mixed to form a sodium-ion battery electrolyte with high flame retardancy, thereby increasing the cycle stability and flame retardancy of the electrolyte; however, the solvent in this scheme is an organic phosphate solvent, which itself has flame retardancy, but its conductivity is inferior to that of carbonate solvents. The phosphate solvent in this scheme is replaced by a carbonate solvent, and the cycle stability and flame retardancy of the sodium-ion battery obtained are unknown. Summary of the invention

[0003] The purpose of the present invention is to solve the problem of how to improve the cycle stability and flame retardancy of a sodium ion battery electrolyte made of a carbonate solvent, and to provide a sodium ion battery flame retardant electrolyte with high cycle stability and a preparation method thereof.

[0004] The present invention improves the flame retardant property of the electrolyte by compounding sulfonic acid-modified carbon black with Zn-MOF, and improves the ion transport property of the electrolyte by loading ionic liquid in the pores of Zn-MOF, thereby improving the cycle stability of the electrolyte.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A flame-retardant electrolyte for sodium ion batteries with high cycle stability, comprising the following components in parts by mass: 70-75% organic ester solvent, 8-12% sodium salt, 2.5-3.5% triethyl phosphate, 4.5-5.5% ionic liquid loaded powder and 5-10% sulfur-containing additive.

[0006] The ionic liquid loaded powder was prepared by the following steps: The composite powder was vacuum dried at 90-100° C. for 6-7 h, and then the composite powder and 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide were mixed in a reactor under nitrogen protection and transferred to an ultrasonic bath for ultrasonic treatment at 70-80° C. for 1-2 h to obtain ionic liquid-loaded powder.

[0007] Further, the organic ester solvent is a mixture of one or more solvents selected from propylene carbonate, butylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, and methyl acetate; The sodium salt is a mixture of one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatoborate), and sodium difluorooxalatoborate; The sulfur-containing additive is at least one of vinyl sulfite, 1,3-propane sultone, cyclopentane sulfone, 1,3-propylene glycol cyclic sulfate, 1,3,2-dioxazolethiophene-2,2-dioxide, and methylene methanedisulfonate.

[0008] Furthermore, the usage ratio of the composite powder to 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide is 2-3 g:1.5-3 g.

[0009] Further, the composite powder is prepared by the following steps: The modified carbon black was ultrasonically dispersed in N,N-dimethylformamide in a reactor, Zn-MOF was added, the temperature was raised to 70-80°C under nitrogen protection, the reaction was stirred for 20-24 hours, and the mixture was filtered through a PTFE membrane after cooling. The mixture was washed with N,N-dimethylformamide, ethanol and deionized water, and then vacuum dried to obtain a composite powder.

[0010] Furthermore, the usage ratio of modified carbon black, N,N-dimethylformamide and Zn-MOF is 1.5-2 g: 100-120 mL: 1.5-2 g.

[0011] Further, the modified carbon black is prepared by the following steps: In a reaction kettle, nano carbon black is ultrasonically dispersed in a 50wt% ethanol solution, 3-mercaptopropyltrimethoxysilane is dissolved in ethanol and then added dropwise to the reaction kettle, the temperature is raised to 60-70°C and stirred for reaction for 20-24h, the precipitate is collected by centrifugation, washed with ethanol and then vacuum dried to obtain pretreated carbon black, the pretreated carbon black is placed in a 20wt% hydrogen peroxide solution, stirred for reaction for 20-24h, 0.5M sodium hydroxide solution is added dropwise until the pH value is greater than 9, the precipitate is collected by centrifugation, washed with deionized water and ethanol, and then vacuum dried at 70-80°C for 20-24h to obtain modified carbon black.

[0012] Furthermore, the usage ratio of nano carbon black, 50wt% ethanol solution, 3-mercaptopropyltrimethoxysilane and ethanol is 3-5g:500-700mL:2-2.5mL:200-250mL; the usage ratio of pretreated carbon black and 20wt% hydrogen peroxide solution is 2-3g:30-50mL.

[0013] Further, Zn-MOF is prepared by the following steps: In a reaction kettle, 2,5-dihydroxyterephthalic acid is dissolved in N,N-dimethylformamide, and then zinc acetate dihydrate is dissolved in deionized water and slowly added dropwise to the reaction kettle. The temperature is raised to 100-110° C. and the reaction is carried out for 20-24 hours. The precipitate is washed after centrifugation and vacuum dried to obtain Zn-MOF.

[0014] Furthermore, the usage ratio of 2,5-dihydroxyterephthalic acid, N,N-dimethylformamide, zinc acetate dihydrate and deionized water is 3.5-5 g: 500-600 mL: 10-15 g: 150-200 mL.

[0015] A method for preparing a flame-retardant electrolyte for a sodium ion battery with high cycle stability comprises the following steps: After the organic ester solvent is mixed in a reactor, the sodium salt, triethyl phosphate, ionic liquid loaded powder and sulfur-containing additive are added into the reactor and mixed thoroughly to obtain a flame-retardant electrolyte for a sodium ion battery with high cycle stability.

[0016] Beneficial effects of the present invention: The flame retardant electrolyte of the sodium ion battery prepared by the present invention has good electrical conductivity, high cycle stability and good flame retardant performance. The flame retardant ability of the flame retardant electrolyte is improved by compounding Zn-MOF and modified carbon black, and the electrical conductivity of the electrolyte is improved by Zn-MOF and the ionic liquid in the Zn-MOF. The prepared ionic liquid powder has high stability and good dispersibility in carbonate solvents.

[0017] The preparation method of the flame-retardant electrolyte for a sodium ion battery of the present invention comprises the following steps: modifying nano carbon black and combining it with Zn-MOF through the reaction of a sulfonic acid group and a hydroxyl group, so that the composite degree of the nano carbon black and the Zn-MOF is uniform, and the nano carbon black is used to fill part of the pores of the Zn-MOF, thereby improving the flame retardant ability of the Zn-MOF and the stability of the Zn-MOF, and loading the ionic liquid in the Zn-MOF, thereby improving the ion transmission ability of the Zn-MOF and the compatibility of the ionic liquid composite powder with a carbonate solvent, so that the dispersibility of the ionic liquid composite powder is good. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1: A flame-retardant electrolyte for sodium ion batteries with high cycle stability, comprising the following raw materials by mass fraction: 70% propylene carbonate, 12% sodium hexafluorophosphate, 3.5% triethyl phosphate, 4.5% ionic liquid supported powder and 10% ethylene sulfite.

[0020] A method for preparing a flame-retardant electrolyte for a sodium ion battery with high cycle stability comprises the following steps: S1. In a reactor, 3.5 g of 2,5-dihydroxyterephthalic acid was dissolved in 500 mL of N,N-dimethylformamide, and then 10 g of zinc acetate dihydrate was dissolved in 150 mL of deionized water and slowly added to the reactor. The temperature was raised to 100 °C and reacted for 20 h. The precipitate was collected by centrifugation, washed with N,N-dimethylformamide, ethanol and deionized water, and dried under vacuum at 80 °C for 10 h to obtain Zn-MOF.

[0021] S2. Ultrasonic disperse 3 g of nano carbon black in 500 mL of 50 wt% ethanol solution in a reactor, dissolve 2 mL of 3-mercaptopropyltrimethoxysilane in 200 mL of ethanol and then add it dropwise to the reactor, heat to 60 ° C and stir to react for 20 h, collect the precipitate by centrifugation, wash with ethanol and then vacuum dry to obtain pretreated carbon black, place 2 g of pretreated carbon black in 30 mL of 20 wt% hydrogen peroxide solution, stir to react for 20 h, add 0.5 M sodium hydroxide solution until the pH value is greater than 9, collect the precipitate by centrifugation, wash with deionized water and ethanol, and vacuum dry at 70 ° C for 20 h to obtain modified carbon black.

[0022] S3. Ultrasonic disperse 1.5 g of modified carbon black in 100 mL of N,N-dimethylformamide in a reactor, add 1.5 g of Zn-MOF, heat to 70 °C under nitrogen protection, stir and react for 20 h, filter with a 0.2 μm PTFE membrane after cooling, wash with N,N-dimethylformamide, ethanol and deionized water, and vacuum dry at 50 °C for 20 h to obtain a composite powder.

[0023] S4. The composite powder was vacuum dried at 90°C for 6 h, and then 2 g of the composite powder and 1.5 g of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide were mixed in a reactor under nitrogen protection, and then transferred to an ultrasonic bath for ultrasonic treatment at 70°C for 1 h to obtain ionic liquid-loaded powder.

[0024] S5. After mixing the organic ester solvent in a reactor, add the sodium salt, triethyl phosphate, ionic liquid loaded powder and sulfur-containing additive into the reactor and mix them thoroughly to obtain a flame-retardant electrolyte for sodium ion batteries with high cycle stability.

[0025] Example 2: A flame-retardant electrolyte for sodium ion batteries with high cycle stability, comprising the following raw materials by mass fraction: 74% organic ester solvent, 10% sodium salt, 3.5% triethyl phosphate, 4% ionic liquid supported powder and 8.5% 1,3-propylene glycol cyclic sulfate.

[0026] The organic ester solvent is a mixture of butylene carbonate and ethylene carbonate.

[0027] The sodium salt is a mixture of sodium perchlorate and sodium tetrafluoroborate.

[0028] A method for preparing a flame-retardant electrolyte for a sodium ion battery with high cycle stability comprises the following steps: S1. In a reactor, 4.5 g of 2,5-dihydroxyterephthalic acid was dissolved in 550 mL of N,N-dimethylformamide, and then 12.5 g of zinc acetate dihydrate was dissolved in 175 mL of deionized water and slowly added dropwise to the reactor. The temperature was raised to 105 °C and the reaction was carried out for 22 h. The precipitate was collected by centrifugation, washed with N,N-dimethylformamide, ethanol and deionized water, and then dried in vacuo at 85 °C for 11 h to obtain Zn-MOF.

[0029] S2. Ultrasonic disperse 4 g of nano carbon black in 600 mL of 50 wt% ethanol solution in a reactor, dissolve 2.25 mL of 3-mercaptopropyltrimethoxysilane in 225 mL of ethanol and then add it dropwise to the reactor, heat to 65 ° C and stir to react for 22 h, collect the precipitate by centrifugation, wash with ethanol and then vacuum dry to obtain pretreated carbon black, place 2.5 g of pretreated carbon black in 40 mL of 20 wt% hydrogen peroxide solution, stir to react for 22 h, add 0.5 M sodium hydroxide solution until the pH value is greater than 9, collect the precipitate by centrifugation, wash with deionized water and ethanol, and vacuum dry at 75 ° C for 22 h to obtain modified carbon black.

[0030] S3. Ultrasonic disperse 1.75 g of modified carbon black in 110 mL of N,N-dimethylformamide in a reactor, add 1.75 g of Zn-MOF, heat to 75 °C under nitrogen protection, stir and react for 22 h, filter with a 0.2 μm PTFE membrane after cooling, wash with N,N-dimethylformamide, ethanol and deionized water, and vacuum dry at 55 °C for 22 h to obtain a composite powder.

[0031] S4. The composite powder was vacuum dried at 95°C for 6.5 h, and then 2.5 g of the composite powder and 2.5 g of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide were mixed in a reactor under nitrogen protection, and then transferred to an ultrasonic bath for ultrasonic treatment at 75°C for 1.5 h to obtain ionic liquid-loaded powder.

[0032] S5. After mixing the organic ester solvent in a reactor, add the sodium salt, triethyl phosphate, ionic liquid loaded powder and sulfur-containing additive into the reactor and mix them thoroughly to obtain a flame-retardant electrolyte for sodium ion batteries with high cycle stability.

[0033] Example 3: A flame-retardant electrolyte for sodium ion batteries with high cycle stability, comprising the following raw materials by mass fraction: 75% organic ester solvent, 8% sodium salt, 2.5% triethyl phosphate, 5.5% ionic liquid supported powder and 9% methylene methane disulfonate.

[0034] The organic ester solvent is a mixture of diethyl carbonate, methyl formate and methyl acetate.

[0035] The sodium salt is a mixture of sodium bis(oxalatoborate) and sodium difluorooxalatoborate.

[0036] A method for preparing a flame-retardant electrolyte for a sodium ion battery with high cycle stability comprises the following steps: S1. Dissolve 5 g of 2,5-dihydroxyterephthalic acid in 600 mL of N,N-dimethylformamide in a reactor, then dissolve 15 g of zinc acetate dihydrate in 200 mL of deionized water and slowly add the mixture dropwise to the reactor. Heat the mixture to 110 °C and react for 24 h. Collect the precipitate by centrifugation, wash the precipitate with N,N-dimethylformamide, ethanol and deionized water, and dry it under vacuum at 90 °C for 12 h to obtain Zn-MOF.

[0037] Zn-MOF contains a large number of unsaturated open metal sites, which are easy for anions to coordinate and bind, weakening the binding effect between sodium ions and their corresponding compounds, thereby improving the ion transport capacity of the sodium ion battery electrolyte and improving the cycle stability of the sodium ion battery.

[0038] S2. Ultrasonic disperse 5 g of nano carbon black in 700 mL of 50 wt% ethanol solution in a reactor, dissolve 2.5 mL of 3-mercaptopropyltrimethoxysilane in 250 mL of ethanol and then add it dropwise to the reactor, heat to 70 ° C and stir to react for 24 hours, collect the precipitate by centrifugation, wash with ethanol and then vacuum dry to obtain pretreated carbon black, place 3 g of pretreated carbon black in 50 mL of 20 wt% hydrogen peroxide solution, stir to react for 24 hours, add 0.5 M sodium hydroxide solution until the pH value is greater than 9, collect the precipitate by centrifugation, wash with deionized water and ethanol, and vacuum dry at 80 ° C for 24 hours to obtain modified carbon black.

[0039] The nano carbon black is treated in a 3-mercaptopropyltrimethoxysilane solution, the mercapto groups are grafted onto the surface of the nano carbon black, and then the mercapto groups are oxidized by hydrogen to obtain sulfonic acid groups. After the oxidation reaction is terminated by sodium hydroxide, the modified carbon black containing sulfonic acid groups on the surface is obtained.

[0040] S3. Ultrasonic disperse 2 g of modified carbon black in 120 mL of N,N-dimethylformamide in a reactor, add 2 g of Zn-MOF, heat to 80 °C under nitrogen protection, stir and react for 24 h, filter with a 0.2 μm PTFE membrane after cooling, wash with N,N-dimethylformamide, ethanol and deionized water, and vacuum dry at 60 °C for 24 h to obtain a composite powder.

[0041] A porous Zn-MOF was synthesized using 2,5-dihydroxyterephthalic acid as a ligand. The modified carbon black was compounded with Zn-MOF to form a composite powder by the reaction between the sulfonic acid group and the hydroxyl group on the surface of the modified carbon black. The sulfonic acid group-modified nano-carbon black and Zn-MOF have a synergistic effect and have good flame retardant properties in carbonate solvents. They can form a carbon layer by promoting rapid crosslinking and coking to achieve flame retardancy. The nano-carbon black has good electrical conductivity and fills part of the pore structure of the Zn-MOF, thereby improving the stability of the composite powder.

[0042] S4. The composite powder was vacuum dried at 100°C for 7 h, and then 3 g of the composite powder and 3 g of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide were mixed in a reactor under nitrogen protection and transferred to an ultrasonic bath for ultrasonic treatment at 80°C for 2 h to obtain ionic liquid-loaded powder.

[0043] The ionic liquid 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide is filled into the pores of the Zn-MOF in the composite powder. The ionic liquid has low flammability, low volatility, and thermal stability, which can improve the flame retardancy and stability of the ionic liquid-loaded powder. The ionic liquid has the ability to coordinate metal ions, which can help the movement and transmission of sodium ions and has good conductivity, which is beneficial to improving the initial efficiency and cycle stability of sodium ion batteries prepared with electrolytes.

[0044] S5. After mixing the organic ester solvent in a reactor, add the sodium salt, triethyl phosphate, ionic liquid loaded powder and sulfur-containing additive into the reactor and mix them thoroughly to obtain a flame-retardant electrolyte for sodium ion batteries with high cycle stability.

[0045] Comparative Example 1: The difference from Example 1 is that in S4, the composite powder is replaced by modified carbon black to prepare the ionic liquid loaded powder.

[0046] Comparative Example 2: The difference from Example 1 is that in S3, nano carbon black is used to replace modified carbon black to prepare a composite powder.

[0047] Comparative Example 3: The difference from Example 1 is that in S5, the ionic liquid-loaded powder is replaced by a composite powder.

[0048] The flame retardant electrolytes for sodium ion batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. The flame retardant ability of the electrolytes was tested by a direct ignition test. The specific operation method was as follows: a 7×15 cm glass fiber strip was immersed in the flame retardant electrolyte for sodium ion batteries for 12 hours, the immersed glass fiber was placed on a glass rod and ignited with an alcohol lamp to observe its flame retardant ability; Prussian blue, polyvinylidene fluoride and conductive carbon black were mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added, the mixture was stirred for 12 hours, and then coated on aluminum foil, dried at 80°C for 12 hours, and cut into positive electrode sheets with a diameter of 14 mm; hard carbon active negative electrode material, sodium carboxymethyl cellulose and conductive carbon black were mixed in a mass ratio of 9:1:1, deionized water was added, stirred for 12 hours, and then coated on aluminum foil, dried at 80°C for 12 hours, and cut into negative electrode sheets with a diameter of 14 mm; the positive electrode sheet, pp separator, sodium sheet, electrolyte and negative electrode sheet were assembled into a CR2016 button battery, and the capacity retention rate of the battery after 200 cycles of charge and discharge was tested.

[0049] The results are shown in Table 1: Table 1: Flame retardant ability and performance test results of sodium ion battery flame retardant electrolyte

[0050] As can be seen from Table 1, the sodium ion battery flame retardant electrolytes prepared in Examples 1 to 3 of the present invention have excellent flame retardant properties, the self-extinguishing time after ignition can be as short as 1.9 s, the flame retardant ability is good, and the capacity retention rate can be maintained at more than 90% after 200 charge and discharge cycles, indicating that the sodium ion flame retardant electrolytes prepared in Examples 1 to 3 of the present invention have high cycle stability.

[0051] In Comparative Example 1, since the modified carbon black was not compounded with Zn-MOF, the synergistic flame retardancy was poor and the ion transmission capacity was poor; in Comparative Example 2, since the carbon black was not modified with sulfonic acid, there was only physical adsorption between the nano carbon black and Zn-MOF, the degree of bonding was uneven, and the bonding strength was not high, resulting in low flame retardancy and ion transmission capacity; in Comparative Example 3, since the ionic liquid was not loaded in the composite powder, the composite powder's transmission capacity for sodium ions was weakened, thereby reducing the electrical cycling stability of the electrolyte.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flame-retardant electrolyte for sodium ion batteries with high cycle stability, characterized in that: By mass fraction, it contains the following components: 70-75% organic ester solvent, 8-12% sodium salt, 2.5-3.5% triethyl phosphate, 4.5-5.5% ionic liquid loaded powder and 5-10% sulfur-containing additive; The ionic liquid loaded powder is prepared by the following steps: The composite powder was vacuum dried at 90-100° C. for 6-7 h, and then the composite powder and 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide were mixed in a reactor under nitrogen protection and transferred to an ultrasonic bath for ultrasonic treatment at 70-80° C. for 1-2 h to obtain ionic liquid-loaded powder.

2. The flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 1, characterized in that: The organic ester solvent is a mixture of one or more solvents selected from the group consisting of propylene carbonate, butylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, and methyl acetate; The sodium salt is a mixture of one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatoborate), and sodium difluorooxalatoborate; The sulfur-containing additive is at least one of vinyl sulfite, 1,3-propane sultone, cyclopentane sulfone, 1,3-propylene glycol cyclic sulfate, 1,3,2-dioxazole thiophene-2,2-dioxide, and methylene methane disulfonate.

3. The flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 1, characterized in that: The usage ratio of the composite powder to 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide is 2-3 g:1.5-3 g.

4. The flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 3, characterized in that: The composite powder is prepared by the following steps: The modified carbon black was ultrasonically dispersed in N,N-dimethylformamide in a reactor, Zn-MOF was added, the temperature was raised to 70-80°C under nitrogen protection, the reaction was stirred for 20-24 hours, and the mixture was filtered through a PTFE membrane after cooling. The mixture was washed with N,N-dimethylformamide, ethanol and deionized water, and then vacuum dried to obtain a composite powder.

5. The flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 4, characterized in that: The usage ratio of the modified carbon black, N,N-dimethylformamide and Zn-MOF is 1.5-2g:100-120mL:1.5-2g.

6. A flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 5, characterized in that: The modified carbon black is prepared by the following steps: In a reaction kettle, nano carbon black is ultrasonically dispersed in a 50wt% ethanol solution, 3-mercaptopropyltrimethoxysilane is dissolved in ethanol and then added dropwise to the reaction kettle, the temperature is raised to 60-70°C and stirred for reaction for 20-24h, the precipitate is collected by centrifugation, washed with ethanol and then vacuum dried to obtain pretreated carbon black, the pretreated carbon black is placed in a 20wt% hydrogen peroxide solution, stirred for reaction for 20-24h, 0.5M sodium hydroxide solution is added dropwise until the pH value is greater than 9, the precipitate is collected by centrifugation, washed with deionized water and ethanol, and then vacuum dried at 70-80°C for 20-24h to obtain modified carbon black.

7. A flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 6, characterized in that: The usage ratio of the nano carbon black, 50wt% ethanol solution, 3-mercaptopropyltrimethoxysilane and ethanol is 3-5g:500-700mL:2-2.5mL:200-250mL; the usage ratio of the pretreated carbon black and 20wt% hydrogen peroxide solution is 2-3g:30-50mL.

8. The flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 7, characterized in that: The Zn-MOF is prepared by the following steps: In a reaction kettle, 2,5-dihydroxyterephthalic acid is dissolved in N,N-dimethylformamide, and then zinc acetate dihydrate is dissolved in deionized water and slowly added dropwise to the reaction kettle. The temperature is raised to 100-110° C. and the reaction is carried out for 20-24 hours. The precipitate is washed after centrifugation and vacuum dried to obtain Zn-MOF.

9. A flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 8, characterized in that: The dosage ratio of the 2,5-dihydroxyterephthalic acid, N,N-dimethylformamide, zinc acetate dihydrate and deionized water is 3.5-5g: 500-600mL: 10-15g: 150-200mL.

10. The method for preparing a flame-retardant electrolyte for sodium ion batteries with high cycle stability according to claim 1, characterized in that: The steps include: After the organic ester solvent is mixed in a reactor, the sodium salt, triethyl phosphate, ionic liquid loaded powder and sulfur-containing additive are added into the reactor and mixed thoroughly to obtain a flame-retardant electrolyte for a sodium ion battery with high cycle stability.

Citation Information

Patent Citations

  • Flame-retardant sodium-ion battery electrolyte and preparation method of safe sodium-ion battery

    CN114464885A

  • High-voltage long-cycle ester-based sodium-ion battery electrolyte and sodium-ion battery

    CN118263527A

  • Sodium-sulfur battery and preparation method thereof

    CN112928262A

  • Preparation method and application of LNO-MOF nano composite material

    CN116751459A

  • Phosphazene modified ionic liquid electrolyte additive as well as preparation method and application thereof

    CN117374393A

Cited By

  • Solid-state electrolyte, solid-state battery and preparation method

    CN120637570A